Validation of the WHOQOL-OLD Module in people cared for in Organizations for the Elderly adult - Molina Napurí, Aurora (2021)
Abstract: WHOQOL-OLD is an instrument designed by the WHO to measure quality of life in older adults. Objective: To validate the WHOQOL-OLD module to evaluate the quality of life of people cared for in organizations for the Elderly in the Miraflores district. Method: The study has a quantitative, non-experimental, cross-sectional approach. The sample design is probabilistic and a sample size of 325 elderly people randomly selected from the three Elderly Care Centers in the district of Miraflores. To validate the WHOQOL-OLD module, the structural equation model was used in three stages detailed in the document. Results: By means of the estimation method by Least Squares of free distribution, the Quality of Life applying the WHOQOL-OLD Module of the WHO, directly and positively influences five of its six factors, with satisfactory adjustment indices (GFI = 0.94 ; SRMR = 0.10; CFI = 0.94; NFI = 0.90; PGFI = 0.70). Conclusions: The WHOQOL-OLD Module of the WHO, it was not possible to validate it completely, since the facet. “Activities in time" did not present the necessary contribution for its validation.